On some restricted plane partition functions - Anand S.; Agarwal A.K (Utilitas Mathematica, 2007)
In this paper, some new restricted plane partition functions are introduced and are associated with n- colour partitions via Agarwal's version of Bender and Knuth bijection. Results obtained here include their generating functions and various combinatorial identities.